TANGGUNG JAWAB HUKUM PENGURUS KOPERASI ATAS KERUGIAN KOPERASI (STUDI KASUS PADA KUD BERKAT RIDHO DESA KIJANG MAKMUR KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR TAHUN 2005-2012) - Restu Dwi Kismawati; Evi Deliana; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The object of study in this study is about the legal responsibilities ofcooperative managers for cooperative losses. Where legal responsibility here isnot only the responsibility to replace the losses suffered by the cooperative, butalso the responsibility to be examined and tried if the case is legally verified.Various cases and previous studies have illustrated that often a legal entity suchas a cooperative suffers losses, including due to errors in terms of management.But as long as the author's observations, often these losses are borne jointly by allmembers, even though these losses are caused by mismanagement by thecooperative management. The purpose of this study is to get an overview of howthe KOPSA management's responsibilities form Thanks to Ridho for cooperativelosses. In addition, how was the effort to complete the law against the KOPSAmanagement, Thanks to Ridho, who had made a loss to the cooperative. Theresearch method used in this study is the Sociological method. The data obtainedis data that describes how the losses incurred in the cooperative are also how theresponsibilities of the cooperative management and how the legal settlement ofthe management has made a loss to the cooperative.Then the data will be analyzed based on existing regulations and concludedin a description. Through in-depth research, this research gets results, that thereare deviations in management, borrowing money without considering thefeasibility and ability of the borrower. The existence of these deviations caused aloss to the KOPSA Thanks to Ridho, but the management was not responsible andresigned from the management. The second thing found in this study, namely themanagement does not hold the principle of healthy lending, because theknowledge and abilities of the management are very weak. Legal settlementefforts are not carried out and an internal resolution is chosen, namely throughCase Bleaching, which is expected to make the cooperative develop againregardless of the shadow of the problem. From this, it can be concluded that thelosses caused by management errors by the management, but here the board didnot want to be responsible at all. Legal remedies can actually be made due tothese deviations, but eventually the case is resolved internally, by carrying outCase Bleaching.Keywords: Responsibility, Administrator, Cooperative and Cooperative Losses